2020
DOI: 10.3389/fmars.2020.00203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Intensity and Light Quality on Diatom Behavioral and Physiological Photoprotection

Abstract: In this study, we investigated the different photoregulation responses of diatom dominated natural biofilms to different light intensities and wavelengths, over a tidal cycle in the laboratory. We compared the overall effect of light spectral quality from its light absorption (Qphar) dependent effect. Two different conditions were compared to study photoprotective strategies: sediment (migrational) and without sediment (non-migrational). Three different colors (blue, green, and red) and two light intensities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 92 publications
(141 reference statements)
2
14
0
Order By: Relevance
“…The dependency of mating on blue light (and to a lower extent green light) in S. robusta and C. didymus 50 is in line with a general propensity of blue light to regulate various cellular processes in diatoms, such as cell cycle progression, phototaxis, vertical migration and production of metabolic compounds such as the pigment marennine 32 , 33 , 36 , 37 , 58 , 76 . The identification of functional red-light phytochromes in diatoms 19 and species-specific red light responses in motility and sinking 37 , 38 , 77 has recently challenged this perspective, suggesting that red light sensing plays a more important role in diatoms than was previously anticipated.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The dependency of mating on blue light (and to a lower extent green light) in S. robusta and C. didymus 50 is in line with a general propensity of blue light to regulate various cellular processes in diatoms, such as cell cycle progression, phototaxis, vertical migration and production of metabolic compounds such as the pigment marennine 32 , 33 , 36 , 37 , 58 , 76 . The identification of functional red-light phytochromes in diatoms 19 and species-specific red light responses in motility and sinking 37 , 38 , 77 has recently challenged this perspective, suggesting that red light sensing plays a more important role in diatoms than was previously anticipated.…”
Section: Discussionsupporting
confidence: 60%
“…Cells generally move upwards towards the sediment surface under moderate light intensities and migrate deeper into the sediment in darkness and under very high light intensities, resulting in synchronized rhythmic migration patterns over diurnal cycles 32 35 . Illumination experiments covering different wavelength ranges have shown that phototaxis and surface accumulation of motile diatoms is in most cases dependent on the presence of blue light 32 , 33 , 36 , 37 . Stauroneis phoenicenteron , on the other hand, is attracted to low intensity red light, suggesting that different benthic species employ different types of photoreceptors 24 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a migration scheme in the GPP algorithm was set according to the observation of the progressive superficial sediment covering by MPB during emersion at our study site (Herlory et al, 2004). However, the migration speed can be faster [a few minutes; see Méléder et al (2003b)] or slower [one hour; see Paterson et al (1998)], and it is mainly controlled by the tidal cycle and the light climate and spectral quality (Pinckney and Zingmark, 1991;Spilmont et al, 2007;Coelho et al, 2011;Barnett et al, 2020;Prins et al, 2020), but also by temperature (Cohn et al, 2003), nutrient availability in the sub-surface of sediment (Kingston, 2002), and desiccation (Coelho et al, 2009). Currently, the GPP-algorithm does not include the short-term variations of MPB photosynthetically active biomass at the sediment surface (i.e., "micro-migrations"), as it has been also observed some days/timings during our field campaigns.…”
Section: Ability Of the Gpp Algorithm To Map The Current Productive Smentioning
confidence: 99%
“…Among abiotic stressors mentioned during the meeting (pesticides, nanoparticles, natural radioactivity…), the expected increase in frequency and intensity of extreme events due to climate change is a concern shared by both freshwater and marine diatomists: parallel works are ongoing to evaluate the effects of heat waves on benthic diatoms of intertidal mudflats and intermittent rivers (Béchet et al 2017). Finally, several contributions have shown that microphytobenthos research is still very active with several ongoing European research projects studying the factors driving biodiversity and the functioning of these benthic microbial communities (Koekodder et al 2019;Prins et al 2020), or the biodiversity and valorisation of the 'blue diatoms' (Poulin et al 2019) and their marennine-like pigments (e.g. Gastineau et al 2018).…”
Section: Editorialmentioning
confidence: 99%